Computer-mediated collaborative learning in a Vietnamese tertiary EFL context : process, product, and learners' perceptions : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Applied Linguistics at Massey University, Palmerston North, New Zealand - Nguyen, Long Van (Massey University, 2011)
Viewing language learning from a sociocultural perspective, this study investigates the nature of both synchronous and asynchronous computer-mediated communication (CMC) and how these two modes of communication may complement each other and contribute to collaborative learning in an EFL classroom environment. The focus is on collaborative language learning competence and learners‟ perceptions of the application of CMC to classroom practices. This classroom-based research took the form of a collaborative problem-solving experiment in a group of EFL students in a large university in Central Vietnam. Various data were collected for the study, including the initial pre-project questionnaire on students‟ background and attitudes, transcripts from both face-to-face and chat discussion, after-chat focus-group interviews, peer comments from both traditional pen-and-paper and wiki exchanges, final collaborative written assignments, and post-project questionnaires and interviews with students about their reflections on classroom CMC in collaborative learning. The study, with both process and product orientation, took place throughout a 12-week semester. Results from the study indicated promising avenues for the application of various CMC technologies in the language classroom. First, although learners‟ language production in the online synchronous discussion was not as high as that from traditional face-to-face practice, the quality of discussion was persuasively better in the SCMC mode. In addition to the fact that learners‟ participation was more equal, evidence of interaction and negotiation leading to a satisfactory level of information synthesis were found to be promising elements in online chatscripts. Second, the use of wikis as a new platform for peer exchanges can be considered an innovation, liberating the students from the conventional, narrow, and linear practice of pen-and-paper-based peer editing. The students participated more, interacted more, and negotiated more in the multi-way interactive architecture of participation, the wiki. Third, although there was no significantly statistical difference in any of the comparative criteria between the two sets of essays produced by the two classes, indications of trends in terms of quality were positive toward the online essays. Fourth, the students‟ reflections on and perceptions of the introduction of CMC into the language classroom presented a potential picture of a technology-enhanced classroom. Apart from the fact that computer and typing skills turned out to be the biggest hindrance regarding the effectiveness of CMC integration, the students‟ reflections on the process were positive and they saw it as constructive. Finally, the four key issues emerging from the study included classroom boundary, the sociotechnical affordances of the CMC environment, the teacher‟s roles in the CMC environment, and product-oriented versus learning-oriented collaborative learning styles.
Keywords: English language learning; Collaborative learning; Computer-mediated communication; Online learning